Exploring the influence of sex and age on the quality and flavor of Huai goat longissimus thoracis et lumborum through transcriptomic and metabolomic analyses - Haoyuan Han; Ziru Kuai; Zhiyun Yao; Xi Lei; Huibin Shi; Jun Li; Kun Liu; Huiru Yin; Yongqing Wang; Kai Quan (BMC Genomics)
Abstract Background The aim of this study was to investigate the effects of age and sex on the composition of fatty acids, amino acids, and vitamins in the longissimus thoracis et lumborum (LTL) of Huai goats. Methods The longissimus thoracis et lumborum tissues of eight Huai goats were collected postslaughter and analyzed for amino acids, fatty acids, and vitamins by gas chromatography‒mass spectrometry (GC‒MS) and standard methods. RNA sequencing (RNA-Seq) was conducted to identify differentially expressed genes (DEGs) across different ages and sexes. Metabolite profiling was performed by liquid chromatography‒mass spectrometry (LC‒MS) to detect and quantify metabolites. Results This study revealed significant differences in amino acid and fatty acid profiles between male and female Huai goats. Compared to females, males presented higher levels of several essential amino acids (e.g., threonine, lysine, and phenylalanine) and nonessential amino acids (e.g., glutamic acid, aspartic acid, and glycine). Additionally, males had higher levels of unsaturated fatty acids such as linoleic acid (C18:2n6c) and arachidonic acid (C20:4n6) compared to those of females. The vitamin B1 content was higher in 6-month-old goats than in 24-month-old goats. Transcriptomic analysis revealed 294 DEGs in the sex group comparison and 580 DEGs in the age group comparison. Key genes involved in collagen production (COL1A1, COL1A2, and COL4A2) and amino acid metabolism (PHGDH and PSAT1) were significantly upregulated in male goats. Functional enrichment analysis revealed significant enrichment in collagen-related Gene Ontology (GO) terms and pathways related to amino acid metabolism. Metabolomic analysis revealed 79 differentially abundant metabolites in the sex group comparison and 69 in the age group comparison, with significant enrichment in pathways related to glycerophospholipid metabolism, oxidative phosphorylation, and amino acid metabolism. Notably, several amino acids and their metabolites, such as lysine, glutamic acid, and serine, exhibited significant differences between male and female goats, which was consistent with the transcriptomic findings. Conclusion The findings indicate that sex and age significantly influence the chemical composition and flavor profile of Huai goat meat. The identified DEGs and differentially abundant metabolites provide a molecular basis for understanding the variations in meat quality and flavor. These results highlight the potential for optimizing meat production practices to increase the quality and flavor of Huai goat meat.